2012
DOI: 10.1152/ajpregu.00357.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of SGLT2 blockade on glomerular and tubular function in the early diabetic rat

Abstract: Thomson SC, Rieg T, Miracle C, Mansoury H, Whaley J, Vallon V, Singh P. Acute and chronic effects of SGLT2 blockade on glomerular and tubular function in the early diabetic rat. Am J Physiol Regul Integr Comp Physiol 302: R75-R83, 2012. First published September 21, 2011 doi:10.1152/ajpregu.00357.2011.-Tubuloglomerular feedback (TGF) stabilizes nephron function from minute to minute and adapts to different steady-state inputs to maintain this capability. Such adaptation inherently renders TGF less efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
215
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(239 citation statements)
references
References 27 publications
15
215
0
Order By: Relevance
“…However, this was dissipated during regular administration, despite a maintained reduction in proximal tubule fluid reabsorption of ≈24%5 because of an adaptive increase in NaCl reabsorption by the loop of Henle via the Na + /K + /2Cl luminal transporter. This adaptation could underlie the increased Na + excretion with bumetanide observed in this study in subjects adapted to a week of dapagliflozin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this was dissipated during regular administration, despite a maintained reduction in proximal tubule fluid reabsorption of ≈24%5 because of an adaptive increase in NaCl reabsorption by the loop of Henle via the Na + /K + /2Cl luminal transporter. This adaptation could underlie the increased Na + excretion with bumetanide observed in this study in subjects adapted to a week of dapagliflozin.…”
Section: Discussionmentioning
confidence: 99%
“…It is approved for the treatment of type 2 diabetes mellitus (T2DM), where it promotes glycosuria 1, 5. T2DM increases the incidence of congestive heart failure (CHF) 6, 7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The albuminuria-lowering effect of SGLT2 inhibition may be due to several mechanisms. First, SGLT2 inhibition achieved through either pharmacological blockade or genetic knockout models reduces renal hyperfiltration, which is considered to be a surrogate marker for intraglomerular pressure in humans [11,12,19,26]. Such a mechanism would be expected to reduce albuminuria independent of changes in systemic BP, similar to the effects of RAAS blockade, but through afferent vasoconstrictive effects rather than efferent vasodilatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in SGLT2 knockout mice, the induction of diabetes was associated with less hyperfiltration compared with wildtype diabetic mice (34). Micropuncture studies in rats with streptozotocininduced diabetes treated with SGLT2 inhibitors demonstrated reductions in proximal sodium reabsorption and in single nephron GFR (35).…”
Section: Sglt2 Inhibitors and Glomerular Hyperfiltrationmentioning
confidence: 95%